2012
DOI: 10.1007/s00276-012-1037-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of the anatomy of the sigmoid colon in developing sigmoid volvulus: a cross-sectional study

Abstract: The study concluded that the lengths of sigmoid colon are not different in living and cadaver subjects but are relatively longer than measurement from western countries. The lengths of sigmoid colon and mesocolon also increases with age and this may possibly be the anatomical basis for the frequent occurrence of sigmoid volvulus and failed colonoscopy among the older population in our environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Alatise et al, reported increase in length of sigmoid colon and mesocolon with age [6]. Yamazaki et al, also found a similar positive correlation while, Sadahiro et al, showed a negative correlation with age [19,20].…”
Section: Age Differencementioning
confidence: 51%
See 3 more Smart Citations
“…Alatise et al, reported increase in length of sigmoid colon and mesocolon with age [6]. Yamazaki et al, also found a similar positive correlation while, Sadahiro et al, showed a negative correlation with age [19,20].…”
Section: Age Differencementioning
confidence: 51%
“…This study describes the morphometric measurements of sigmoid loop in cadavers which have found to be not different from living subjects as reported by Alatise et al, [6]. The sigmoid colon length and the height and width of sigmoid mesocolon were assessed at two levels, one being with regard to pelvic brim and the other in relation to mesenteric root.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical sign of an acute sigmoid volvulus in plain X-rays is the “coffee bean sign”, while in an abdominal CT scan, the characteristic “whirl sign” as well as an dilated colon with air/fluid level can be detected [11, 12]. Those radiologic findings are due to the torsion of the often long and redundant sigmoid colon around its elongated mesenteric axis what finally causes intestinal obstruction [13]. …”
Section: Introductionmentioning
confidence: 99%